Treatment Strategy in Atrial Tachycardia Originating From the Atrial Appendage - Hai-Yang, Xie; Zi-Cong, Feng; Xiao-Gang, Guo; Qi, Sun; Jian-Du, Yang; Jian, Ma (Frontiers in Physiology, 2022)
Background: Atrial appendage tachycardia (AAT) originating from the atrial appendage (AA) is extremely difficult to eliminate using radiofrequency catheter ablation (RFCA). The optimal management strategy for AAT refractory to RFCA remains unclear. Objective: This study aims to investigate the long-term result of ablative therapy and the optimal alternative management for AAT refractory to RFCA. Methods: A total of 51 patients with AAT originating from the AA undergoing RFCA were recruited. Video-assisted atrial appendectomy and oral ivabradine were performed on those with AATs refractory to RFCA, and this study aimed to evaluate their safety and long-term efficacy. Results: We included 51 patients (51/586, 8.7%) with AATs confirmed by activation mapping and contrast venography. Among them, there were 28 (54.9%) AATs originating from the distal AA. In total, 14 (27.4%) AATs were refractory to RFCA, including 13 originating from the distal AA and one arising from the proximal AA. Ten of 11 (90.9%) AATs originating from the distal AA were eliminated after an atrial appendectomy, and the other three AATs were suppressed using oral ivabradine. Origins from the distal AA refractory to RFCA and early age of AAT onset ≤26.5 years indicated the need for atrial appendectomy. No major complications occurred, and nine patients with tachycardia-induced cardiomyopathy fully recovered. Long-term success was achieved in 98.0% of patients with multiple treatment managements. Conclusion: AATs originating from the distal AA were more refractory to RFCA. RFCA was the cornerstone of AAT catheter ablation. Video-assisted thoracoscopic atrial appendectomy was an effective strategy for those origins at the distal AA and the age of AAT onset ≤26.5 years. Ivabradine represents a promising treatment for AAT temporarily in pediatric and young adult patients.